The Roman Period Name for Adel. (2nd May 2016) - Wilson, Pete
ABSTRACT: Antiquarian and more recent discussions of Roman period place-names in western West Yorkshire are considered, along with possible locations for Cambodunum, with the Roman period site at Adel identified as the latter.